Linguistic Borrowing in the English Language of Economics - Magdalena Bielenia-Grajewska (Lexis: Journal in English Lexicology)
The aim of this paper is to discuss the function of loanwords in English economic discourse. In the introductory part, the author presents very briefly an inventory of foreign words used in English. Being a linguist and an economist, the author is interested in the language of economics and she will try to show how different languages have helped to shape the current economic lexicon in English. In this article, an attempt will be made to discuss which languages have influenced English economic vocabulary and which particular domains, such as technical analysis or options, rely heavily on loanwords. The author also discusses how borrowed lexical items determine the language of economics. The article finishes with an attempt to predict the future situation of borrowings in English business communication.